2018
DOI: 10.1055/s-0036-1589529
|View full text |Cite
|
Sign up to set email alerts
|

Claisen Rearrangements of Benzyl Vinyl Ethers and Heterobenzyl Vinyl Ethers

Abstract: The Claisen rearrangement of benzylic substrates (benzyl vinyl­ ethers) has received considerably less attention than its well-known aliphatic and normal aromatic variants. Here, we review the rearrangement of both benzylic and heterobenzylic substrates, with examples of the reaction’s use in the synthesis of natural products and drug-like molecules.1 Introduction2 Early Attempts at the Benzyl-Claisen Rearrangement3 Successful Benzylic Examples4 Heterobenzylic Examples5 Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The process is energetically highly demanding due to the disruption of aromatic stabilization upon [3,3] sigmatropic shift, as evidenced by the harsh reaction conditions required to rearrange allyl phenyl ether. Even more challenging is the benzyl version of the aromatic Claisen, which suffers from a competing [1,3] sigmatropic rearrangement . Indeed, an earlier study found that benzyl vinyl ether is resistant to undergo rearrangement at temperatures below 260 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The process is energetically highly demanding due to the disruption of aromatic stabilization upon [3,3] sigmatropic shift, as evidenced by the harsh reaction conditions required to rearrange allyl phenyl ether. Even more challenging is the benzyl version of the aromatic Claisen, which suffers from a competing [1,3] sigmatropic rearrangement . Indeed, an earlier study found that benzyl vinyl ether is resistant to undergo rearrangement at temperatures below 260 °C .…”
Section: Introductionmentioning
confidence: 99%
“…[3,3]-Sigmatropic rearrangements have already become a significant strategy to create new chemical bonds and incorporate various functionalities in a complex setting . Among these rearrangements, Cope and hetero-Cope rearrangements have particularly attracted considerable attention from synthetic chemists .…”
mentioning
confidence: 99%